GENERALIZATION OF THE MAIN METHODS FOR THE TREATMENT OF NATURAL GAS WITH A HIGH CONTENT OF CARBON DIOXIDE - Matkivskyi, S. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
Today, the bulk of natural gas production is provided from fields that are to some extent depleted, and most of them are at the final stage of development. The structure of residual hydrocarbon reserves deteriorates over time due to the fact that hydrocarbons are extracted mainly from the active part of the reserves of the fields. Hydrocarbons that are located in flooded reservoirs, tight reservoirs and depleted reservoirs located below the edge of the profitability of their production are classified as hard-to-recover. Due to the lack of efficient technologies, the development of these reserves is currently being carried out at a very slow pace. The search for optimal ways of extracting residual reserves is the main problem, the need to solve which is becoming increasingly important against the background of deterioration in the quality and structure of hydrocarbon reserves. A promising direction for maintaining the level of hydrocarbon production is the development of reservoirs, the reservoir gas of which is characterized by a high content of carbon dioxide. Preparation of hydrocarbon products from such fields can be carried out in different ways. The most well-known methods for cleaning production gas from carbon dioxide include absorption, adsorption methods, as well as their combinations. Analysis of world practice shows that absorption processes using amines are the most effective for the treatment of large flows of hydrocarbons. Aqueous solutions of ethanolamine, diethanolamine, and triethanolamine have found wide application as a working agent. The use of the latest technologies for the preparation of hydrocarbons with a high carbon dioxide content will increase the efficiency of the development of proven hydrocarbon reserves. Investing in the introduction of modern technologies for the development of hydrocarbon reservoirs will increase their production capabilities and significantly reduce the burden on the environment.